Towards New Security Primitives Based on Hard AI Problems - Zhu, Bin Benjamin; Yan, Jeff (Int. Workshop on Security Protocols, 2013)
Many security primitives are based on hard mathematical problems. Using hard AI problems for security is emerging as an exciting new paradigm (with Captcha being the most successful example). However, this paradigm has achieved just a limited success, and has been under-explored. In this paper, we motivate and sketch a new security primitive based on hard AI problems.